The Impact of Knowledge Management (KM) Strategies on Employee Job Satisfaction: A Study of RMG in Bangladesh (Global Journal of Management and Business Research, 2021)
Knowledge management (KM) strategy is a crucial part of personnel management and retention of talents. This paper aims at identifying the impact and relation of knowledge management on employee satisfaction. The study is based on hypothesis and the data was collected by a questionnaire survey from 35 employees of reputed garments organization of Bangladesh. Satisfactions rely on factors like compensation structure, user friendly, relation with co-worker, autonomy, workload etc. The core findings of the study is codified strategy is more user friendly, but the practice of tacit strategy with proper incentives increase the overall satisfaction of employee though there are more workload. The employees are more comfortable with tacit strategy than codified strategy. The study is only focused on garments employee where KM strategy is widely practice all spheres of Human Resource Management (HRM). However, The paper reveal how KM strategy can increase employee satisfaction. The HR people and decision maker can understand and design appropriate KM strategy from this study. Therefore, organization also can manage and retain the talents by designing and applying findings of the study.
Keywords: KM strategy; satisfaction; codified; bangladesh